O protagonismo da biblioteca escolar: ratificando (ou não) a importância do espaço para a promoção da cultura letrada - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
School environment has got a space that is supposed to be of privilege to the formation of readers. Unfortunately, it is not what can be seen every day in Brazilian education institutes. Either there is space, but there are not books; or there is both space and books, but there is not pedagogical proposals that bring students closer to the books, raising their interest for reading. In the view of this problem, this research assumes that a well-structured library, with up-todate collections and didactical proposals well defined for motivating reading, can collaborate significantly to the formation of readers at schools. Thus, this research has the aim of revitalizing the public library of the elementary school A Mão Cooperadora, located in the town of Itaituba-Pará, in order to check whether there has been an increase in the formation of reader and what resulting benefits of that contact through the library were. This study is of interpretive and intervention nature, and is made up of three fundamental phases: exploratory, filed research and analysis of material and is supported mainly by the studies of Britto (2012; 2015); Candido (2011); Silva (1984; 1993); Santos (2016); Bértolo (2014); Milanesi (2013) and Todorov (2014). The production and analysis of data used the procedures of qualitative research, by using the following tools: journal, images log, questionnaires and interviews. The research is linked to Programa de Mestrado Profissional em Letras – Profletras, of Universidade Federal do Oeste do Pará – Ufopa, and has had The Library William Gabriel with an archive of three thousand books about world literature. Research results have revealed significant expansion in the library attendance by junior and senior elementary students in the library, developing reading and text comprehension skills, as well as an improvement in the interaction and humanization of students.
Keywords: Leitura; Literatura; Biblioteca Escolar; Cultura Letrada; CNPQ:: Lingüística, Letras e Artes; diversidade social e práticas docentes; Linguagens e Letramentos